ChemInform Abstract: Fischer—Tropsch Catalysts for the Production of Hydrocarbon Fuels with High Selectivity. Issue 28 (15th July 2014) - Zhang, Qinghong; Cheng, Kang; Kang, Jincan; Deng, Weiping; Wang, Ye
Abstract Review: 94 refs.